VD_FINDINFO HC / 2011 / 133 vom 19. Januar 2011 - VD Tribunal cantonal (2011)
CONTRAT DE TRAVAIL, TRANSFERTEN GÉNÉRAL, RÉSILIATION EN TEMPS INOPPORTUN | 324a CO, 333 CO, 336c CO, 306 al. 2 CPC, 452 CPC, 456a CPC, 27 LJT, 46 al. 2 LJT, 47 LJT